2019
DOI: 10.1016/j.jadohealth.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Short Message Service Reminders to Parents for Increasing Adolescent Human Papillomavirus Vaccination Rates in a Secondary School Vaccine Program: A Randomized Control Trial

Abstract: A B S T R A C TPurpose: In Victoria (Australia), the human papillomavirus (HPV) vaccine is delivered within a state-wide secondary school vaccine program, administered by local government. This study aimed to test the hypothesis that sending a short message service (SMS) reminder to parents who had consented to their child's receiving the HPV vaccine would lead to greater uptake of the vaccine within the program. The secondary aim was to assess the effect of self-regulatory versus motivational message content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 31 publications
0
56
0
Order By: Relevance
“…Some studies investigated interventions to improve HPV vaccine uptake but each of them was evaluated separately [1823]. Other studies and recommendations on factors influencing VC integrated the evaluation of many interventions but rarely specific for HPV vaccine, that is critical for the variety of targets and healthcare professionals implicated in vaccine counselling, the involvement of parents, and the relevance of indications including cancers [2427].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies investigated interventions to improve HPV vaccine uptake but each of them was evaluated separately [1823]. Other studies and recommendations on factors influencing VC integrated the evaluation of many interventions but rarely specific for HPV vaccine, that is critical for the variety of targets and healthcare professionals implicated in vaccine counselling, the involvement of parents, and the relevance of indications including cancers [2427].…”
Section: Discussionmentioning
confidence: 99%
“…Organizational aspects to improve HPV vaccine uptake were also investigated, in particular the implementation of immunization services' accessibility, the role of reminder systems, and communication technologies. Nevertheless, previous evaluations were rarely comprehensive or specific, thus compromising the estimate of the effect of interventions' interaction and the consideration of HPV vaccine peculiarities (i.e., the variety of involved targets and healthcare professionals, the role of parents, and the range and seriousness of HPV-related diseases, including cancers) [18–29].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that incorporating ease and procedural justice principles in a letter asking a driver to attend a medical examination increased compliance with the request by 23 percent (Faulkner et al ). Similarly, the Victorian Department of Health and Human Services has used INSPIRE to increase vaccination rates (Borg et al 2018; Tull et al ). Borg and colleagues (2018) found that sending a letter designed using INSPIRE principles informing parents of Aboriginal children about a free influenza vaccination increased their vaccination rates by 34 percent.…”
Section: Discussionmentioning
confidence: 99%
“…Borg and colleagues (2018) found that sending a letter designed using INSPIRE principles informing parents of Aboriginal children about a free influenza vaccination increased their vaccination rates by 34 percent. Tull et al () found that sending an SMS message developed using INSPIRE techniques (specifically, implementation intentions) to parents of secondary school students increased the percentage of students who received the human papillomavirus vaccine. Furthermore, members of the authorship team, along with their colleagues at BehaviourWorks Australia, Monash University, have been invited to deliver INSPIRE training sessions to a range of Australian government agencies, many of whom have gone on to use INSPIRE principles in their written materials.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for adolescent vaccination, however, reminders produce moderate increases in vaccination rates: a Cochrane review found only a 7% increase in vaccination rates from reminders across 10 studies with 30,868 participants [15][16][17]. Preliminary evidence suggests reminder effectiveness may be boosted with strategies like allowing parents to request a clinic call back, including educational information, and combining reminders with other interventions such as phone calls or navigator home visit [12,13,15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%